RNA therapeutics in targeting G protein-coupled receptors: Recent advances and challenges - Wanjun Yuan; Xiangyang Shi; Leo Tsz On Lee (Elsevier, 2024)
G protein-coupled receptors (GPCRs) are the major targets of existing drugs for a plethora of human diseases and dominate the pharmaceutical market. However, over 50% of the GPCRs remain undruggable. To pursue a breakthrough and overcome this situation, there is significant clinical research for developing RNA-based drugs specifically targeting GPCRs, but none has been approved so far. RNA therapeutics represent a unique and promising approach to selectively targeting previously undruggable targets, including undruggable GPCRs. However, the development of RNA therapeutics faces significant challenges in areas of RNA stability and efficient in vivo delivery. This review presents an overview of the advances in RNA therapeutics and the diverse types of nanoparticle RNA delivery systems. It also describes the potential applications of GPCR-targeted RNA drugs for various human diseases.